F-center impact on F-Center Impact on Photoelectrochemical Properties in Hematite - Stashans, A. (2009)
Structural and optical properties of F-center (two electrons trapped by an oxygen vacancy) defect in hematite have been studied using a quantum-chemical model. Calculated absorption energies, 0.9 eV and 3.6 eV, are discussed in terms of the available experimental data. An explanation for the origin of experimentally observed electron depletion in hematite is proposed. © 2010 World Scientific Publishing Company.